2013
DOI: 10.1088/0953-2048/26/9/095001
|View full text |Cite
|
Sign up to set email alerts
|

Electrical measurements of AC losses in high temperature superconducting coils at variable temperatures

Abstract: Measurements of AC losses in high temperature superconducting (HTS) coils wound from two different types of YBa 2 Cu 3 O 7 (YBCO) coated conductors are reported. AC loss measurements by different arrangements of voltage loops and pick-up coils were investigated to propose accurate and convenient techniques to measure the AC losses in HTS coils, especially for large coils with the measurement signals significantly higher than the input range of typical lock-in amplifiers. A new and simple sub-cooling technique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Previous studies have shown that AC loss in HTS windings with AC transport current of amplitude It and coil critical current Ic follows a power law ∝ ( ⁄ ) where the exponent n is between 2 and 4 [2][3][4][5][6][7][8][9][10]. By fitting our experimental data, we find that the loss varies with current according to a power law with exponent approximately 2.3 to 2.6 which is in accordance with previously reported values [2][3][4][5][6][7][8][9][10][11].…”
Section: B Coil Assembly Ac Loss Measurementsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous studies have shown that AC loss in HTS windings with AC transport current of amplitude It and coil critical current Ic follows a power law ∝ ( ⁄ ) where the exponent n is between 2 and 4 [2][3][4][5][6][7][8][9][10]. By fitting our experimental data, we find that the loss varies with current according to a power law with exponent approximately 2.3 to 2.6 which is in accordance with previously reported values [2][3][4][5][6][7][8][9][10][11].…”
Section: B Coil Assembly Ac Loss Measurementsupporting
confidence: 91%
“…On the other hand, by using REBCO wire rather than BSCCO in a coil winding, there is the potential to reduce the AC loss in the coil winding. As a result, the literature is replete with reports of experimental and modelling studies on windings using either BSCCO or REBCO wire [2][3][4][5][6][7][8][9][10]. However, there are far fewer reports of hybrid coil assemblies employing either mixed wire types, or separate wires with different critical current, that are deliberately apportioned within the winding assembly.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, by using REBCO wire rather than BSCCO in a coil winding, there is the potential to reduce the AC loss in the coil winding. As a result, the literature is replete with reports of experimental and modelling studies on windings using either BSCCO or REBCO wire [2][3][4][5][6][7][8][9][10]. However, there are far fewer reports of hybrid coil assemblies employing either mixed wire types, or separate wires with different critical current, that are deliberately apportioned within the winding assembly.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, intensive AC loss analysis of HTS coils has been carried out both experimentally and numerically [14][15][16][17][18][19][20]. However, there has been no report to date on the influence of asymmetric wire critical current on coil AC loss.…”
Section: Introductionmentioning
confidence: 99%